If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 29 = 83 Reorder the terms: 29 + x = 83 Solving 29 + x = 83 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + x = 83 + -29 Combine like terms: 29 + -29 = 0 0 + x = 83 + -29 x = 83 + -29 Combine like terms: 83 + -29 = 54 x = 54 Simplifying x = 54
| 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 | | 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 | | 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 | | -.5=4-4.5x | | 4x+(-3)=1 | | 11q=33 | | y=0.80(55)+136 | | 4x+(-3)=2 | | 8x-2=-9+7y | | .3(3x+6)=8x+10 | | 5(6+3x)=105 | | -5y+6=y+9 | | (-9-12)x=8-4x | | y=0.80(45)+136 | | 5x+-2x+5x=8 | | 20/(-4)=c |